Medication-related burden and associated factors among diabetes mellitus patients at Felege Hiwot Comprehensive Specialized Hospital in northwest Ethiopia - Bekalu, Abaynesh Fentahun; Yenit, Melaku Kindie; Tekile, Masho Tigabe; Birarra, Mequanent Kassa (Frontiers in Clinical Diabetes and Healthcare, 2022)
Background: Evaluating medicines burden from patients’ perspective is essential for getting good health outcome of diabetes mellitus (DM) management. However, data are limited on this sensitive area. Thus, the study was aimed to determine the medication-related burden (MRB) and associated factors among DM Patients at Felege Hiwot Comprehensive and Specialized Hospital in Northwest Ethiopia (FHCSH). Methods: A cross-sectional study was conducted on 423 systematically selected DM patients attending the DM clinic of FHCSH from June to August 2020. The medication related burden was measured by using Living with Medicines Questionnaire Version-3 (LMQ-3). Multiple linear regression was used to identify factors associated with medication related burden and reported with a 95% Confidence Interval (CI). P-value <0.05 was considered as statistically significant to declare the association. Results: The mean LMQ-3 score was 126.52 (±17.39). Majority of the participants experienced moderate 58.9% (95% CI: 53.9-63.7) to high 26.2% (95% CI: 22.5-30.0) degrees of medication burden. Nearly, half 44.9% (95% CI: 39.9-49.7) of the participants were non-adherent to their prescribed medications. VAS score (B = 12.773, p = 0.001), ARMS score (B = 8.505, p = 0.001), and fasting blood glucose (FBS) on visit (B = 5.858, p = 0.003) were significantly associated with high medication related burden. Conclusion: Significant number of patients were suffered from high medication related burden and non-adherence to long term medicine. Therefore, multidimensional intervention to decrease MRB and to upgrade adherence is required to increase patient’s quality of life.